EVALUASI SISTEM DRAINASE PERKOTAAN DI KAWASAN KOTA METROPOLIS SURABAYA - Riman, - (WIDYA TEKNIKA, 2011)
Surabaya is centre of many activities such as governmental, political, economical, social and cultural and many others. This has made rapid growth of the people of Surabaya. To give sufficient public services, it needs utilities such as clean water, waste water, streets, transportations, drainages, etc. Lacking of drainage has caused flood in Surabaya every year. In order to solve that problem, an integrated development planning of drainage is needed. The planning involves activities such as doing identification, processing, evalution and analysis of the problem occurs in each district. The output can be used as a guidance to plan development of city utilities in Surabaya.